Effect of different body measurements on body weight of pre-weaning Duroc pigs using Principal Analysis Component Approach - Amao, S.R. (Nigerian Journal of Animal Science, 2023)
The body measurements of pigs are the important part of precision in livestock farming that closely related to the growth characteristics and traits. It is significant for monitoring and understanding the pig growth at different stages effectively for better selection with the procedure of Principal Component Analysis (PCA) to identify and visualize better traits among the measured parameters. The records of 50 piglets comprising of 20 male and 30 female pigs were used with weekly measurement on body weight (BW), body length (BL), heart girth (HG), heart at withers HW, ear length (EL), pelvic width (PW), tail length (TL) and hock circumference (HC). The obtained data was subjected to PCA and the results observed were highly correlated s among most of the morphometric and growth traits. Kaiser-Meyer-Olkin measure of sampling adequacy, Bartlett’s Test of Sphericity and communality were calculated. Two PCs were extracted while these PCs accounted for 88.48% and PC1 had 74.21% and PC2 amounted to 14.28% variance, respectively of total variance. PC1 was represented by high loading of BW, BL, HG, HW, EL, PW, TL and HC. PC2 had medium to high loading for PW, TL and HC. PC1 seemed to explain the body of pig whereas PC2 seemed to represent just the few variables of the pig. It can be concluded that traits described by PC1 can be based line for pig improvement. The accounted PCs at different stage may be exploited in breeding and selection programmes to acquire highly coordinated animal bodies using fewer measurements.